2007
DOI: 10.1007/s00520-007-0333-9
|View full text |Cite
|
Sign up to set email alerts
|

Living with cancer and perception of care: Icelandic oncology outpatients, a qualitative study

Abstract: Reactions to the diagnosis of cancer indicate strong emotional reactions. A strong will to handle the situation and determination to maintain normality in life was prominent. Establishment of positive patient-health care professional relationships, caring encounters, faith, believing in treatment and support from family was highly valued as support and giving hope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 38 publications
1
29
1
Order By: Relevance
“…In an Icelandic study on cancer patients undergoing treatment, the disease and treatment trajectory are seen as a family matter, indicating the importance of the spouse. 50 Research suggests that the support of a spouse is considered as more helpful than professional help in dealing with difficult emotions. The family was also considered being more important during the diagnostic and treatment period than the support of friends.…”
Section: Qol and Depressioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In an Icelandic study on cancer patients undergoing treatment, the disease and treatment trajectory are seen as a family matter, indicating the importance of the spouse. 50 Research suggests that the support of a spouse is considered as more helpful than professional help in dealing with difficult emotions. The family was also considered being more important during the diagnostic and treatment period than the support of friends.…”
Section: Qol and Depressioncontrasting
confidence: 56%
“…The family was also considered being more important during the diagnostic and treatment period than the support of friends. 50 Failing to see differences in QOL depending on gender and marital status in the present study is surprising but might be explained by the variability within the sample, representing diverse types of cancer and different stage of disease resulting in few cases behind each group.…”
Section: Qol and Depressionmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies found that patients’ treatment experiences were positively influenced by staff who were responsive, courteous and able to meet the individual's information needs and that nurse‐led care was influential to the well‐being outcomes of patients at various stages of the treatment pathway (Edvardsson, Watt, & Pearce, ; Larsson, Sahlsten, Sjostrom, Lindencrona, & Plos, ). Similarly, Hjörleifsdóttir, Hallberg, Gunnarsdóttir, and Bolmsjö () found that the caring responses of nurses was associated with increased patient satisfaction, while social interactions based on close relationship bonds and familiar routines may positively contribute to the individual's well‐being (Bahrami, ). Furthermore, the number, interconnectedness and quality of the patient's relationships and support networks have been linked to better adjustment to cancer (Hoffman et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] In this context it is important to consider that cancer patients form an ex tremely vulnerable group because their disease is often life-threatening and because cancer and its treatment have an enormous impact on their private, social, and professional lives. [22][23][24][25][26] Studies have shown that patients and nursing staff do not always agree on the importance of caring behaviours; 12,[27][28][29][30] the greatest discrepancies in this regard can be found in oncology care. 29 It is therefore important to come to a better understanding of the characteristics of a good nurse from the perspective of cancer patients.…”
Section: Introductionmentioning
confidence: 99%